Enhancing University Students’ English Speaking through MALL: Integrating the Practice English Speaking Talk Application - Anis Setiyanti; Suharsiwi Suharsiwi (English Language in Focus (ELIF), 2026)
English has become a global lingua franca that plays a crucial role in academic, professional, and intercultural communication, leading higher education institutions to emphasize English speaking competence as an essential graduate skill. However, many university students still experience considerable difficulties in speaking English fluently due to limited vocabulary, pronunciation challenges, lack of confidence, and insufficient exposure to authentic communication environments. The rapid advancement of mobile technology has introduced Mobile-Assisted Language Learning (MALL) as an innovative pedagogical approach that enables flexible, autonomous, and interactive language learning. This study aims to enhance university students’ English-speaking ability through the integration of the Practice English Speaking Talk application within a MALL framework using a Classroom Action Research design. The research involved 32 undergraduate students and was conducted in two cycles consisting of planning, acting, observing, and reflecting stages, with data collected through speaking performance tests, classroom observations, interviews, and learning documentation. The findings indicate significant improvement in students’ speaking competence, with the average speaking score increasing from 58.1 in the pre-cycle stage to 68.8 in Cycle I and further improving to 79.9 in Cycle II. Student participation increased from 46% to 88%, while speaking confidence improved from 40% to 85%, alongside improvements in fluency, pronunciation accuracy, vocabulary mastery, grammatical competence, participation, confidence, and learner autonomy. These findings suggest that mobile-assisted speaking applications provide an effective pedagogical solution for enhancing communicative competence in higher education English instruction.